2023
DOI: 10.1101/2023.02.24.529734
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pro-inflammatory polarization and colorectal cancer modulate alternative and intronic polyadenylation in primary human macrophages

Abstract: Macrophages are essential cells of the immune system that alter their inflammatory profile depending on their microenvironment. Alternative polyadenylation in the 3prime UTR (3prime UTR-APA) and intronic polyadenylation (iPA) are mechanisms that modulate gene expression, in particular in cancer and activated immune cells. Yet, how polarization and colorectal cancer (CRC) cells microenvironment affect 3prime UTR-APA and iPA in primary human macrophages remains unknown. Here, primary human monocytes were isolate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 118 publications
(151 reference statements)
0
1
0
Order By: Relevance
“… 36 Recently, Wilton et al reported an increase in V2, but not V1 or V3, in primary human macrophages as they were polarized into a pro-inflammatory state or were co-cultured with cancer cells. 63 This finding also suggests that V2 might contribute to macrophage anti-tumor activity. This is not surprising, given that V2 can increase autophagic activity and that autophagy regulates many macrophage functions, such as antigen presentation 64 and several other functions.…”
Section: Discussionmentioning
confidence: 85%
“… 36 Recently, Wilton et al reported an increase in V2, but not V1 or V3, in primary human macrophages as they were polarized into a pro-inflammatory state or were co-cultured with cancer cells. 63 This finding also suggests that V2 might contribute to macrophage anti-tumor activity. This is not surprising, given that V2 can increase autophagic activity and that autophagy regulates many macrophage functions, such as antigen presentation 64 and several other functions.…”
Section: Discussionmentioning
confidence: 85%